Aplicação da simulação de Monte Carlo no valuation da empresa Engie Brasil Energia - Pinto, Gabriel (2022)
Valuation is the process of calculating the value of an asset, being applied in determining the value of stocks, portfolio management, merger and acquisition process, etc. In this paper, the Discounted Cash Flow (DCF) method was employed, which calculates the intrinsic value of an asset, based on assumptions related to cash flow projections. In order to capture the uncertainties related to these assumptions, the Monte Carlo Simulation (MCS) was incorporated into the model, being performed a comparative analysis between the results obtained in the DCF model and the results of the model that incorporates the MCS in the DCF. For the adoption of premises, a study was held about the electric sector and the evaluated company, Engie Brasil Energia, the largest private electric power generator company in Brazil in 2022. Excel and the VBA programming language were used in the modeling, and the data were obtained from the Engie Brasil Energia website. With the DCF, a valuation of 44.17 BRL per share was calculated, and by incorporating MCS into the DCF, a probability distribution of the value per share was obtained with an average value of 43.78 BRL. It was concluded that by applying the MCS to the DCF, a more comprehensive view of the company's value is achieved by considering the impact of the uncertainties of the assumptions